The end of dieting eaudiobook How to live for life. - Fuhrman, Joel (2014)
In The End of Dieting, Joel Fuhrman M.D., a board–certified family physician who specializes in preventing and reversing disease through nutritional and natural methods, and #1 New York Times bestselling author of Eat to Live, Super Immunity and The End of Diabetes, delivers a powerful paradigm-shifting book that shows us how and why we never need to diet again. Fuhrman writes, "By reading this book, you will understand the key principles of the science of health, nutrition and weight loss. It will give you a simple and effective strategy to achieve—and maintain—an optimal weight without dieting for the rest of your life. This new approach will free you forever from a merry-go-round of diets and endless, tedious discussions about dieting strategies. This is the end of dieting."